Field verification of low-level biochar applications as effective ameliorants to mitigate cadmium accumulation into Brassica campestris L from polluted soils - Zhang, Youchi; Liu, Shuang; Lin, Shanna; Reid, Brian J.; Coulon, Frederic; Cai, Chao (Frontiers in Environmental Science, 2023)
Cadmium(Cd) has been recognized as a significant contributor to the pollution of farmland soils in China, and biochars have been reported to be effective in mitigating soil Cd pollution. However, most of these studies were conducted in laboratory or greenhouse settings. Furthermore, in general, unrealistically large amounts of biochar (>10 t/ha) have been used in previous researches. In this study, three biochars: rice straw biochar (RS), pig manure biochar (PM) and rice husk biochar (RH) were produced from readily available farm residues and characterized. These were used in a field experiment, at low applications rates of 1.8 and 3.6 t/ha, with rape (Brassica campestris L.). Batch adsorption experiments indicated Cd adsorption in the order RS biochar > PM biochar > RH biochar. Field experiment indicated biochar amendments to slightly changes in soil pH and CEC; yet led to considerable and significant decreases in extractable Cd concentrations (reductions of: 43%-51% (PM), 29%-35% (RS) and 17%-19% (RH)). Reduced extractable Cd correlated with lower Cd concentrations in rape plants. PM and RS biochars were the most effective in decreasing Cd phytoaccumulation into edible parts of rape (>68% reduction). It is highlighted that biochars were produced using a pyrolysis unit with an output of 20 ton/yr. Thus, assuming a working application rate of 2 ton/ha, the pyrolysis unit could service 10 ha/yr. While at a modest scale, this research demonstrates the genuine reality of biochar-based remediation solutions to contribute to the mitigation of diffuse Cd contamination in some of China’s impaired farmland.